NON-LINEAR CREEP OF PMMA: SERVICE PERFORMANCE PREDICTION FROM SHORT-TERM TESTS - André, José Reinas (2007)
In previous literature, empirical models have been applied to describe and predict the viscoelastic behavior of polymer materials. For example, the empirical power-law model seems to fit well, but only for short-term data [1, 2, 3]. Such formulations are of some utility in data reduction and extrapolation, but do not allow meaningful physical interpretations and lack generality. When we look at the dynamic behavior of polymers, we recognize the presence of a very large variety of possible and specifiable processes (responses), spanning an extremely wide range of frequencies and cluster sizes within the structure, at any given temperature. That range significantly widens and shifts to lower and lower frequencies (and larger and larger cluster sizes) as the temperature is lowered.